Chemical Composition and Antibacterial Activity of Essential oil of Mentha longifolia Leaf from Albaha Area Southern Saudi Arabia - Burham, Bader Omer; Osman, Osman Ali; Nour, Azhari Abdelhafeedh Mohammed (Asian Journal of Biological and Life Sciences, 2019)
The essential oil obtained by hydrodistillation from the leaves of Saudi Arabia nativeMentha longifolia(Lamiaceae) was analyzed by gas chromatography-mass spectrometry GC/MS. Forty six compounds were analysed, it was characterized by a high percentage of oxygenated monoterpenes (30.40%) with Piperitone as the major one (30.77%), followed by sesquiterpen hydrocarbons (26.08%) in which Caryophellene (5.58%) as the main, while monoterpene hydrocarbons (23.90%) with gamma-Terpinene (1.36%) as a main. The principal components ofM. longifoliaoil was the piperitone with chemical formula C10H14O. The antibacterial activity of the essential oil ofM. longifoliaL. leaf were evaluated in this study. The essential oil showed strong antibacterial activity againstBacillus subtiliswith inhibition zone (25mm) andEscherichia coli(24mm), It seems that the essential oils derived from theMentha longifoliaL. oil could be used as a natural source of antimicrobial agents.
Keywords: Antibacterial; Essential oil; GC/MS analysis; Mentha longifolia; Monoterpenes; Saudi Arabia